Finance and Development, March 1996. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1996)
The design of payment systems has important implications for the conduct of monetary policy, the soundness of financial firms, and the functioning of the economy as a whole.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet